A prospective clinical trial to evaluate the role of very low dose mifepristone 10 mg in medical management of uterine leiomyoma in tertiary care hospital from North West India - Kochar, Swati; Suthar, Neha; Chaudhary, Shweta; Chandad, Shahnaj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Uterine leiomyomas are the most common benign tumours of the uterus and also the most common benign solid tumor in female. It arises from the uterine smooth muscles (myometrium) but contain varying amount of fibrous connective tissue. Aim of study was to evaluate the efficacy of very low dose Mifepristone (10 mg) on leiomyoma volume and its related symptoms. Methods: This was a prospective clinical study. 30 women met with the inclusion criteria and giving informed consent for the study. Results: Mean myoma volume was 60.32±51.89 at initial visit and 36.13±48.54 at 3 months follow up visit with 40.1% reduction which was statistically significant difference (p < 0.001). Mean PBAC score in Group I was 155.53±21.70 at initial visit and 0.97±2.97 at 3 months follow up visit with 99.3% reduction which was statistically significant (p < 0.001). Conclusions: Mifepristone 10 mg is efficacious in term of control of bleeding, alleviation of pain related symptoms with few side effects. So low dose mifepristone can be used as a suitable option for women with symptomatic fibroids in perimenopausal periods or patients not willing or fit for surgery.